Knowledge of Nonmedical Individuals about Cardiopulmonary Resuscitation in Case of Cardiac Arrest: A Cross-Sectional Study in the Population of Jeddah, Saudi Arabia - Fadi Jandali Qara; Loui K. Alsulimani; Maged M. Fakeeh; Diyaa H. Bokhary (Emergency Medicine International)
Introduction. In cardiac arrest victims, providing a high-quality cardiopulmonary resuscitation (CPR) is a fundamental component of initial care, especially in the out-of-hospital settings. In this study, we sought to assess the knowledge of nonmedical people regarding cardiopulmonary resuscitation in the case of out-of-hospital cardiac arrest. Methods. A cross-sectional survey containing 22 questions was administered to individuals aged ≥ 18 years, who were not health care providers. Sample included residents of Jeddah, Saudi Arabia. The survey included knowledge about cardiac arrest findings, previous experience with CPR, knowledge of basic life support (BLS), and concerns related to CPR. Results. The fully completed survey forms of 600 respondents were analysed. Out of these, 28.7% stated that they had previously received training in CPR. Regarding manifestations of cardiac arrest, 40.7% suggested loss of consciousness, 36.8% suggested cessation of breathing, and 24.7% suggested cessation of circulation. Only 11.7% among respondents were found to be able to perform chest compressions. Also, only 9.2% could perform mouth-to-mouth ventilation, and 29.5% were able to perform both. While 55.5% knew the location for performing chest compressions, 44.7% knew the correct depth, and only 18.5% knew the correct compression–ventilation rate. Bystander CPR had been performed by only 10.7%. Conclusion. In our sample, we found lack of knowledge regarding CPR. We advise for a coordinated national effort to improve the public awareness about CPR performance. This may include mass education, specialized training, and setting legislations.